The Effect of Liquidity Risk on Bank Performance: Moderating Effect of Board Size and Board Meeting - Indira Nuansa Ratri (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
Bank performance is the most important thing to note and interesting to study because it plays a crucial role in a country's economy. This study aims to determine the effect of liquidity on bank performance and the moderating effect of the size and board meeting. The test in this study uses multiple linear regression on conventional banks listed on the Indonesia Stock Exchange from 2014 to 2019. The results of this study indicate that liquidity has a positive effect on bank performance, the size of the board of commissioners weakens the positive effect of liquidity on bank performance, and the number of board meeting weaken the positive effect of liquidity on bank performance.